Sustainable finance: the economic impacts of environmental, social and governance (ESG) factors on stock price, brand value and executive compensation - Ding, H (2022)
Environmental, social, and governance (ESG) disclosure is increasingly important for listed companies, representing a key factor that contributes to sustainable finance. However, whether and how the inclusion of ESG scores in investment decisions affects stock prices remains uncertain; the effect of ESG on intangible assets is a neglected area of investigation, and not all executives in global capital markets respond to ESG issues. Moreover, how each of the three dimensions of ESG affects the value of a company has yet to be fully determined. For the first time, this study takes Chinese listed companies from 2014 to 2018 as a sample to examine the impact of ESG on stock price, brand value, and executive compensation. These three main research objectives constitute three independent papers of this DPhil thesis, which address the motivation to engage in ESG disclosure and provide insight into the important role of ESG in financial markets, as well as how investors, entrepreneurs, and board members consider ESG strategies.